2021
DOI: 10.1016/j.jtct.2021.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Responses following a Single Dose of SARS-Cov-2 Vaccination in Allogeneic Stem Cell Transplantation Recipients

Abstract: Immunocompromised individuals were not included in formal trials of SARS-CoV-2 mRNA vaccines. Subsequent studies in patients with haematological malignancies and solid organ transplant recipients suggest inferior responses to vaccination. We determined antibody responses to a single dose of vaccines in one of the most vulnerable patient groups, allogeneic haematopoietic cell transplant (allo-HCT) recipients. Pfizer-BioNTech or AstraZeneca SARS-CoV-2 vaccines were administered at least 3 months post-transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 12 publications
(12 reference statements)
4
32
0
1
Order By: Relevance
“…Older age and concurrent immunosuppression were significantly associated with lack of response. 14 Overall, our present study confirms that most of the transplanted patients respond to a complete vaccination cycle. Responders in the allogeneic group had even higher antibody levels than HC.…”
supporting
confidence: 85%
“…Older age and concurrent immunosuppression were significantly associated with lack of response. 14 Overall, our present study confirms that most of the transplanted patients respond to a complete vaccination cycle. Responders in the allogeneic group had even higher antibody levels than HC.…”
supporting
confidence: 85%
“…However, among patients with malignancies (10,11) and recipients of solid organ transplantation (12)(13)(14) emerging data suggest lower vaccine efficacy compared to the healthy population. Data for patients undergoing cellular therapies are sparse, with small studies reporting attenuated humoral and/or cellular immune responses (15)(16)(17). We therefore aimed to assess immune responses to mRNA COVID-19 vaccines among patients who underwent cellular therapies at our center, with the goal of identifying predictors of response, determining the ideal timing for vaccination, and to identify patients at high risk for non-protective immune responses who might benefit from additional doses ('boosters') of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 article was included through snowballing. This resulted in 10 articles being suitable for this analysis, which are shown in Table 3 in order of timing of the vaccination post-HSCT [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was also seen in the available response rates for COVID vaccination: 37–50% <12 months post-HSCT [ 48 , 56 ] versus 68–94% >12 months post-HSCT [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. One study reported on vaccination < 6 months post-HSCT with only 12.5% response ( n = 8) [ 57 ]. In addition to timing, usage of immunosuppressants and active GVHD seem to be the most important factors influencing response.…”
Section: Resultsmentioning
confidence: 99%